2020
DOI: 10.30994/jqph.v3i2.87
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Work Accidents Based on K3 Knowledge and Work Behavior at Muhammadiyah Hospital in Ponorogo

Abstract: Occupational health and safety is a component of the hospital that must be considered by the hospital. The purpose of his research was to find out related to the occurrence of work accidents based on knowledge of occupational safety and health and the behavior of workers at the Muhammadiyah Hospital. The sampling technique was done by proportional cluster random sampling with a cross sectional approach. The population of all employees working at the Muhammadiyah Hospital. The independent variable is knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…Occupational Health and Safety is one of the topics that is never finished being discussed in various parts of the country. The existence of the World Health Organization (WHO) is proof that the health sector has a "special place" for serious discussion, Occupational health and safety is a component of the hospital that must be considered [13] Mojorejo village as a place for woven bamboo craftsmen, to discuss and develop in several aspects, namely improving the quality of handicraft products, increasing product marketing, developing business partnerships, utilizing capital loan facilities [9]…”
Section: Resultsmentioning
confidence: 99%
“…Occupational Health and Safety is one of the topics that is never finished being discussed in various parts of the country. The existence of the World Health Organization (WHO) is proof that the health sector has a "special place" for serious discussion, Occupational health and safety is a component of the hospital that must be considered [13] Mojorejo village as a place for woven bamboo craftsmen, to discuss and develop in several aspects, namely improving the quality of handicraft products, increasing product marketing, developing business partnerships, utilizing capital loan facilities [9]…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with Yuda's research there is a significant relationship between knowledge and personal hygiene behavior of the community. This means that if people's knowledge is getting better, their personal hygiene behavior will also be getting better [11] In another study, namely the results of research, showed that there was an influence of knowledge on occupational safety and health on the incidence of work accidents (significant value = 0.002 <0.05), there was an influence of behavior on the incidence of work accidents (significant value = 0.004 <0 ,05) [12] 2. Attitude All triangulation informants said that washing hands and feet needs to be done after work.…”
Section: Discussionmentioning
confidence: 99%
“…Keselamatan dan Kesehatan Kerja (K3) merupakan salah satu dari fungsi manajemen SDM yang juga perlu untuk diperhatikan oleh perusahaan, khususnya bagi perusahaan dengan risiko kecelakaan yang tinggi ( Gamal et al, 2018). Upaya Keselamatan dan Kesehatan Kerja (K3) bertujuan untuk mengurangi risiko kecelakaan yang terjadi di lokasi kerja serta untuk menciptakan tempat kerja yang aman, efisien, dan produktif (Diannita et al, 2020;Pulungan, 2020). Upaya Keselamatan dan Kesehatan Kerja (K3) dapat berupa kesesuaian beban kerja, perilaku kerja, dan lingkungan kerja yang bertujuan untuk menciptakan rasa aman tanpa risiko yang membahayakan karyawan di tempat kerja (Diannita et al, 2020).…”
Section: Grafik 2 Perencanaan Sumber Daya Manusiaunclassified